Near-IR period-luminosity relations for pulsating stars in [Omega] Centauri (NGC 5139) - Navarrete, Camila; Dékány, István (Astronomy and astrophysics, 2017)
Aims. The globular cluster ω Centauri (NGC 5139) hosts hundreds of pulsating variable stars of different types, thus representing a treasure trove for studies of their corresponding period-luminosity (PL) relations. Our goal in this study is to obtain the PL relations for RR Lyrae and SX Phoenicis stars in the field of the cluster, based on high-quality, well-sampled light curves in the near-infrared (IR).Methods. Observations were carried out using the VISTA InfraRed CAMera (VIRCAM) mounted on the Visible and Infrared Survey Telescope for Astronomy (VISTA). A total of 42 epochs in J and 100 epochs in KS were obtained, spanning 352 days. Point-spread function photometry was performed using DoPhot and DAOPHOT crowded-field photometry packages in the outer and inner regions of the cluster, respectively.Results. Based on the comprehensive catalog of near-IR light curves thus secured, PL relations were obtained for the different types of pulsators in the cluster, both in the J and KS bands. This includes the first PL relations in the near-IR for fundamental-mode SX Phoenicis stars. The near-IR magnitudes and periods of Type II Cepheids and RR Lyrae stars were used to derive an updated true distance modulus to the cluster, with a resulting value of (m − M)0 = 13.708 ± 0.035 ± 0.10 mag, where the error bars correspond to the adopted statistical and systematic errors, respectively. Adding the errors in quadrature, this is equivalent to a heliocentric distance of 5.52 ± 0.27 kpc.
Im Titel ist Omega als griechischer Buchstabe dargestellt
Gesehen am 18.10.2017